Pioneering Prolonged Release: A Novel Pellet-Based Approach to Anti-Anginal Therapy of Ranolazine - Chakraborty, Tanushree; R, Suma.; Khanum, Aisha; Khan, Tahir Ahmed; Khan, Sarvar (Indian Journal of Pharmaceutical Education and Research, 2026)
Aim: Angina is a clinical syndrome with symptoms attributed to myocardial ischaemia. There are many class of drugs which are used to manage it, among such is ranolazine which acts by inhibiting late Na+ current. Ranolazine is used for the treatment of recurrent angina. So, the aim of the present work was to develop prolonged release pellets incorporated into capsules. Materials and Methods: In the present study, pellets were prepared by the Extruder and Spherodizer equipment using polymer Eudragit L 100, Eudragit S 100, HPMC K15M and red iron oxide using (120, 125, 130 mg) for Eudragit L100, likewise for the other polymers. The concentration of polymers was varied in all the preparations. Results and Conclusion: The effect of polymers was tested to check the prolonged effect by the help of in vitro studies. The FT-IR results indicated that Ranolazine and the other excipients were compatible. The pellets were subjected to different pharmacopoeial tests like tap density, bulk density, rate of flow, angle of repose, microscopic particle, weight variation, drug content and in vitro release studies. The in vitro release studies were carried out using USP type- I dissolution apparatus, i.e. basket type. Which showed that formulation F1 (Drug, Eudragit L100, Mannitol, MCC) showed the best sustained release for a period of 11 hrs. Hence, we conclude the main aim of the envisaged research work is achieved, i.e. sustaining the release of ranolazine without dose dumping.
Keywords: Ranolazine; Sustained Release Pellets; Extrusion and Spheronization; Pelletization